The Routledge Handbook of Transnational Organized Crime - Allum, Felia; Allum, Felia, 1971-; Gilmour, Stan (London; New York; Routledge, Taylor and Francis, 2022)
"This fully revised new edition provides a definitive and holistic overview of Transnational Organized Crime (TOC) in a world in which right wing populism has gained ground, trade wars are increasing, and China is an emerging force. Updated to reflect the changing world environment the book includes new chapters on issues such as criminal network analysis, environmental crime, cybercrime, people smuggling, drugs activities in the modern world, the relationship between organised crime and corruption, anti-organised crime resilience and the effectiveness of the fight against organised crime. New country case studies have also been included. The Handbook is presented in six sections: Theories, definitions and laws Origins and manifestations Contagion and Evolution Intensity and Impact Governance Reaction and Future Truly interdisciplinary in nature the Handbook features contributions from an international team of experts, working in different academic disciplines and within varied law enforcement agencies. It will appeal to scholars, policy-makers, and practitioners in International Law, Global Governance, International Political Economy and Security Studies"--
First edition published in 2011.
Includes bibliographical references and index.
Keywords: Transnational crime; Organized crime